Effective mine risk education in war-zone areas - a shared responsibility - Gillieatt, Sue; Durham, J.; Sisavath, B. (Oxford University Press, 2005)
The focus of this paper is effective health education and promotion in the field of mine awareness, or what has more recently been re-titled mine risk education. According to the United Nations, mine risk education comprises educational activities that aim to reduce the risk of injury from landmine/unexploded ordnance (UXO) through raising awareness and promoting behavioural change and includes public information dissemination, education and training, and community mine action liaison.Specifically, this paper is an empirical study of mine risk education practices using data collected during the implementation of a mine risk education programme that commenced in Lao PDR in 1996 and is ongoing. In particular, it considers lessons learned from the programme's monitoring and evaluation process. The authors argue that in a country such as Lao PDR, where communities have lived with UXO infestation for over 25 years, more mine risk education is not necessarily needed. This paper concludes that common programmes of mine risk education using top-down educational methods, based on the assumption that ignorance of landmine/UXO risk is the key factor in mine accidents, are inadequate. Evidence from the literature on health promotion and the experience of the programme indicate that that there is a need to supplement or replace existing common mine risk education practices with techniques which incorporate an understanding of the economic, social and political circumstances faced by communities at risk.